Ecological safety of the urbanized territories under conditions of technogenic transformation of atmospheric precipitations - Герецун, Галина Михайлівна (Eastern-European Journal of Enterprise Technologies, 2014)
Formation conditions of ecological hazard of urbanized territories under the influence of atmospheric precipitations are analyzed in the paper. Self-consistent control scheme of ecological safety of precipitations is developed. It includes the stages of identification of hazards, formation of databases and making managerial decisions. The analysis of identification features of hazardous factors that cause ecologically hazardous precipitations is conducted. The features of atmospheric precipitations as the object of the ecological safety assessment are described. The choice of acidity index of precipitations in the city of Chernivtsi as an environmental hazard indicator is justified. The model scheme of interaction of natural and anthropogenic factors in the formation of ecologically hazardous sediments is developed. The influence of wind conditions on the environmental safety of precipitations is determined. In particular, it is shown that, in Chernivtsi north-west winds have the greatest influence on the formation of the ecological hazard of atmospheric precipitations. The contribution of stationary and mobile sources to the technogenic transformation of precipitations is analyzed. The role of transport networks and automotive pollution in the formation of roadside areas of high ecological hazard of precipitations is shown. It is found that, in Chernivtsi contribution of mobile sources to the overall picture of air pollution is consistently high and ranges from 91,6-92,3 %. Herewith, 60.4 % of the total emissions of sulfur oxides, 93 % of nitrogen oxides and 97.4 % of carbon oxide is formed due to mobile sources. This in turn leads to the formation of local areas of environmentally hazardous precipitations.